1992
DOI: 10.1159/000267169
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Cells Secrete Urokinase-Type Plasminogen Activator and Its Inhibitor PAI-1

Abstract: Secretion of plasminogen activators and their inhibitors was examined in cultures of human retinal pigment epithelial (RPE) cells. The methods employed were zymography and reverse zymography, solid-phase immunocapture assay, metabolic labeling followed by immunoprecipitation, and immunofluorescence. The results showed that these cells produce urokinase-type plasminogen activator (u-PA) and a plasminogen activator inhibitor (PAI) which is immunologically and biochemically similar to PAI-1. Tissue-type plasminog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although not documented here, the pre dominant type of PAI produced by human RPE cells is PAI-1, identified with monoclon al antibody which neutralizes the inhibitory activity of PAI-1 [17].…”
Section: Solid-phase Enzyme Immunoassay For Active Pai-1 and U-pa In mentioning
confidence: 80%
See 2 more Smart Citations
“…Although not documented here, the pre dominant type of PAI produced by human RPE cells is PAI-1, identified with monoclon al antibody which neutralizes the inhibitory activity of PAI-1 [17].…”
Section: Solid-phase Enzyme Immunoassay For Active Pai-1 and U-pa In mentioning
confidence: 80%
“…Plasminogen-activation-mediated proteo lysis in human RPE cells seems to be affected by various factors, including the number of cell passages [17], phagocytosis of microbeads [37], certain growth factors [38], and retinoids [39], Our results indicate that both IFN-a and IFN-y have a potent stimulatory effect on u-PA-mediated plasminogen activation by human RPE cells in culture.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…ProuPA can be converted to active enzyme by traces of plasmin initiating the plasminogen activation cascade. We have recently demonstrated that uPA staining in cultured human RPE cells was localized to focal contact sites at the leading edges of cultured subconfluent RPE cells [12], a distribution typical of migrating cells [18]. TGF-ß is produced by most cultured cells in a latent form which can be converted to the biologically active molecule by plasmin [19].…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of uPA and uPAR activity is involved in proliferation, migration and invasive growth of many cell types [8][9][10]. We and others have shown that human RPE cells in culture secrete uPA and its inhibitor PAI-1 [11,12]. We have also reported that interferon-Á (IFN-Á) enhanced uPA activity in RPE cells due to the suppressed PAI-1 mRNA expression [13].…”
Section: Introductionmentioning
confidence: 99%